2016
DOI: 10.3389/fpsyg.2016.00623
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Temperament, Sensory Processing, and Motor Coordination in 3-Year-Old Children

Abstract: Poor motor skills and differences in sensory processing have been noted as behavioral markers of common neurodevelopmental disorders. A total of 171 healthy children (81 girls, 90 boys) were investigated at age 3 to examine relations between temperament, sensory processing, and motor coordination. Using the Japanese versions of the Children's Behavior Questionnaire (CBQ), the Sensory Profile (SP-J), and the Little Developmental Coordination Disorder Questionnaire (LDCDQ), this study examines an expanded model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
15
0
4
Order By: Relevance
“…Parental perception of temperament and self-regulation of the infant is a valuable predictor of the development of attention in children who are born preterm (Van de Weijer-Bergsma, Wijnroks, & Jongmans, 2008). However, few studies have examined temperament in children born preterm (Cassiano & Linhares, 2015; Cosentino-Rocha et al, 2014; Klein, Gaspardo, & Linhares, 2011; Klein, Gaspardo, et al, 2009; Montirosso et al, 2016; Nakagawa, Sukigara, Miyachi, & Nakai, 2016; Poehlmann et al, 2011).…”
mentioning
confidence: 99%
“…Parental perception of temperament and self-regulation of the infant is a valuable predictor of the development of attention in children who are born preterm (Van de Weijer-Bergsma, Wijnroks, & Jongmans, 2008). However, few studies have examined temperament in children born preterm (Cassiano & Linhares, 2015; Cosentino-Rocha et al, 2014; Klein, Gaspardo, & Linhares, 2011; Klein, Gaspardo, et al, 2009; Montirosso et al, 2016; Nakagawa, Sukigara, Miyachi, & Nakai, 2016; Poehlmann et al, 2011).…”
mentioning
confidence: 99%
“…It is, therefore, understood that a deficit of executive functions can have devastating effects on activities of daily life that could be interpreted as human occupations in a broad sense, such as school activities, self-care, play, leisure, and social participation ( 11 , 16 , 17 ). A typical development of executive functions is considered to be a protective factor in various neurodevelopmental disorders ( 18 , 19 ). By contrast, children with executive function deficits are highly likely to be diagnosed with a neurodevelopmental disorder in the future ( 18 , 19 ).…”
mentioning
confidence: 99%
“…A typical development of executive functions is considered to be a protective factor in various neurodevelopmental disorders ( 18 , 19 ). By contrast, children with executive function deficits are highly likely to be diagnosed with a neurodevelopmental disorder in the future ( 18 , 19 ). It has been observed that the sensory symptoms of school-aged children with autism are affected by the degree of cognitive maturity of the children ( 9 , 20 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Na idade escolar, as crianças com problemas de processamento e integração da informação sensorial tendem a desenvolver dificuldades na escrita, na manutenção da atenção para o aprendizado acadêmico e na tendência ao isolamento, por evitar esportes de grupo (AYRES, 1972;DEMAIO-FELDMAN, 1994;BLANCHE, 2005). Bakker e Moulding (2012), Farrow e Coulthard (2012) e Nakagawa et al (2016) mostram, em seus estudos, que alteração no processamento sensorial pode ainda estar associado a sintomas psicológicos negativos e dificuldades de temperamento em crianças e adultos. Blanche (2005), ao avaliar uma população de adultos com sinais de processamento sensorial deficiente na infância, observou que essas alterações se mantêm ao longo da vida e influenciam as escolhas ocupacionais dos indivíduos, que podem ter suas atividades limitadas, se não tratado.…”
Section: Discussionunclassified